A22: Consensus Treatment Plans for Induction Therapy in Childhood Proliferative Lupus Nephritis—Status of Use in Daily Clinical Care. Issue 11 (March 2014) - von Scheven, Emily; Punaro, Marilynn; Ardoin, Stacy P.; Brunner, Hermine; Hsu, Joyce J.; Mehta, Jay; Wagner‐Weiner, Linda; Klein‐Gitelman, Marisa; Rouster Stevens, Kelly; Haines, Kathleen A.; Schanberg, Laura; Eberhard, B. Anne
Abstract : Background/Purpose: Consensus treatment plans (CTPs) serve as an alternative strategy to randomized controlled trials for assessing treatment effects. The CTPs for induction therapy of childhood proliferative lupus nephritis (cLN) were developed for use in clinical care; they are based on best available evidence and endorsed by CARRA Pediatric Rheumatologists. They specify two options for immunosuppressive therapy (IV Cyclophosphamide (CP) and oral Mycophenolate (MMF)) and three options for steroid therapy (primarily oral regimen, primarily IV regimen and mixed oral/IV regimen). The purpose of this pilot study was to assess the use of and adherence to the cLN‐CTPs, and to estimate rates of renal response and safety and tolerability. Preliminary results are presented here. Methods: Providers at 14 participating CARRA sites agreed to utilize the induction cLN‐CTPs for eligible patients. Eligible patients were <20 years old and had biopsy‐proven newly diagnosed proliferative cLN; however the CTPs were not intended for patients with concurrent infections, pregnancy or other severe SLE manifestations that would dictate specific therapies different from the cLN‐CTPs. Patients were invited to enroll in the CARRA registry for periodic collection of standard clinical SLE and renal outcome measures. Results: To date, 71 potential SLE patients with newly diagnosed proliferative cLN were cared for at 13 sites (87% female, mean age 14.6 yrs, mixed ethnicity [37% Hispanic] and race [41% Caucasian, 30% African American, 9% Asian, 20% other/unknown]). 41 (58%) patients were enrolled in the CARRA registry, a prerequisite for study participation. Reasons for non‐enrollment in the registry included failure of being approached in a timely fashion (34%), patients/parents declined participation (4%), and failure to complete consent due to not speaking English (1%). Among the 41 patients who were enrolled in the registry, 29 (43%) were treated according to one of the cLN‐CTPs. For induction immunosuppressive therapy, providers selected the CP CTP for 61%, and the MMF CTP for 39% of patients. For induction steroid therapy, providers selected the primarily IV regimen for 43%, mixed IV/oral regimen for 35%, and primary oral regimen for 17% of the patients. Reasons for not using one of the options specified in the CTPs included patients not meeting eligibility characteristics for their use (35%), providers choosing not to use the cLN‐CTP (13%), treatment initiated at another institution (7%), and the prescribing physician being unaware of the cLN‐CTPs (1.5%). Conclusion: A minority of patients with newly diagnosed proliferative cLN received therapy according to the cLN‐CTPs, which are considered the best therapeutic regimen based on available scientific evidence and expert opinion. Important outcome data from many patients was missed by patients not being approached for enrollment in the registry. This suggests that additional efforts are necessary to promote implementation of the cLN‐CTPs as we endeavor to perform comparative effectiveness studies and improve the prognosis for children with cLN.